Human Papillomavirus Vaccination and Social Media: Results in a Trial With Mothers of Daughters Aged 14–17 - Buller, David B.; Pagoto, Sherry; Henry, Kimberly; Berteletti, Julia; Walkosz, Barbara J.; Bibeau, Jessica; Baker, Katie; Hillhouse, Joel; Arroyo, Kelsey M. (Frontiers in Digital Health, 2021)
Introduction Parents acquire information about HPV vaccines online and encounter vaccine-critical content, especially on social media, which may depress vaccine uptake. Materials and Methods This is a secondary analysis from a randomized trial of a Facebook-delivered adolescent health campaign targeting mothers in 34 states (N=869). The Facebook groups differed in that 15% of posts in one were focused on indoor tanning (IT) and 15% in the other, on prescription drug misuse. In both groups, posts promoted HPV vaccination (n=38 posts) and vaccination for other disease (e.g., influenza, n=49). Mothers completed surveys at baseline and 12- and 18-month follow-up to assess HPV vaccine uptake. Reactions (like, sad, angry, etc.) and comments to each HPV-related post were counted and coded. Results Initiation of HPV vaccination (1 dose) was reported by 63.4% of mothers at baseline, 71.3% at 12-week posttest (pre/post p<0.001) and 73.3% at 18-month posttest (pre/post p<0.001). Completion of HPV vaccination (2 or 3 doses) was conveyed by 50.2% of mothers at baseline, 62.5% at 12-week posttest (pre/post p<0.001), and 65.9% at 18-month posttest (pre/post p<0.001). For posts on HPV vaccines, 8.1% of mothers reacted (n=162 total), and 68.4% of posts received a reaction (63.2% like; 13.2% love, 7.9% sad). Also, 7.6% of mothers commented (n=122; 51 unfavorable, 68 favorable, and 1 neutral), and 50.0% of these posts received a comment. There were no differences in pre-post change in vaccine status by count of reactions or comments to HPV vaccine posts (Ps>0.05). Baseline vaccination was associated with the valence of comments to HPV vaccine posts (7.2% of mothers whose daughters had completed the HPV series at baseline made a favorable comment but 7.6% of mothers whose daughters were unvaccinated made an unfavorable comment). Conclusions Effective strategies are needed in social media to promote HPV vaccines and counter misinformation about and resistance to them. Mothers whose daughters complete the HPV vaccine course might be recruited as influencers on HPV vaccines, as they may be predisposed to talk favorably about the vaccine. Comments from mothers who have not vaccinated should be monitored to ensure that they do not spread vaccine-critical misinformation.